Mirror image properties in human languages - Kida, Ireneusz (Slavia Centralis, 2020)
In this paper I discuss the phenomenon of mirror image properties in human languages. I give examples from English, Polish, Malay, Gothic, Latin and Classical Greek. Although I take into consideration only a few languages, my paper has further implications, namely, that mirror image properties exist in any language of the world. I start with a description of the natural phenomenon of mirror image and then extend my discussion to language. I talk about mirror image sentences, reduplication, and palindromes.